2023
DOI: 10.1002/acn3.51840
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of a relationship between sleep spindles and treatment response in epileptic encephalopathy

Abstract: ObjectiveEpileptic encephalopathy with spike‐wave activation in sleep (EE‐SWAS) is a challenging neurodevelopmental disease characterized by abundant epileptiform spikes during non‐rapid eye movement (NREM) sleep accompanied by cognitive dysfunction. The mechanism of cognitive dysfunction is unknown, but treatment with high‐dose diazepam may improve symptoms. Spike rate does not predict treatment response, but spikes may disrupt sleep spindles. We hypothesized that in patients with EE‐SWAS: (1) spikes and spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Frthermore, as it is clearly shown in the epilepsy population, pathology can disturb the sleep architecture in such a way that sleep stages, as such, might not be classifiable anymore. A microstructural approach [presence of spindles (25,26), rapid eye movements (27) or cyclic alternating pattern (28)] or spectral power analysis are then helpful but are often still combined with sleep staging. Complete unsupervised learning could reveal intrinsic patterns, however, translating these patterns into clinically relevant information will be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Frthermore, as it is clearly shown in the epilepsy population, pathology can disturb the sleep architecture in such a way that sleep stages, as such, might not be classifiable anymore. A microstructural approach [presence of spindles (25,26), rapid eye movements (27) or cyclic alternating pattern (28)] or spectral power analysis are then helpful but are often still combined with sleep staging. Complete unsupervised learning could reveal intrinsic patterns, however, translating these patterns into clinically relevant information will be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep spindle rate has been reported to be decreased in autism, developmental delay, and attention deficit hyperactivity disorder 40,41 and correlate with cognitive abilities in children with dyslexia 42 and epilepsy 8 . Critically, several studies have found that medications and interventions that increase sleep spindles improve memory consolidation, and medications that disrupt spindles impair memory consolidation 9,[43][44][45] , suggesting a mechanistic link between sleep spindles and memory performance. Further supporting sleep spindles as generalizable biomarker for sleep-dependent memory processes across ages and conditions, we find that focal spindle rate predicts sleep dependent memory consolidation on a motor procedural task in healthy children and children with focal epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of cognitive dysfunction in RE is an area of active research. We recently discovered that epileptiform spikes interfere with sleep spindles, prominent bursts of 9-15 Hz oscillations mechanistically linked to memory consolidation during stage 2 sleep 6,7 , in RE and severe sleep activated epileptic encephalopathies [8][9][10] . In contrast to measures of spike rate, sleep spindle rate predicts IQ, processing speed, and sensorimotor coordination in RE 8 , and changes in spindle rate predict cognitive response to high-dose benzodiazepine treatment in severe epileptic encephalopathies 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation